ANALYSIS OF FACTORS CAUSING OUT-OF-SCHOOL CHILDREN OF PRIMARY EDUCATION AGE IN BRAJA LUHUR VILLAGE, BRAJA SELEBAH DISTRICT, EAST LAMPUNG REGENCY IN 2021 - Rizki Karunia (Journal Learning Geography, 2022)
The aims of this study to determine what factors are the causes of children dropping out of school in Braja Luhur Village in 2021. The research method used in this research is descriptive quantitative. The population in this study were all out of school children in Braja Luhur Village, both elementary and junior high schools in 2021 as many as 50 children. Then this study is a population study that includes the entire population that is the sample in this study, namely as many as 50 dropouts, both elementary and junior high school levels. Then data collection using technical questionnaires and technical documentation. Data analysis used percentage analysis technique. The results of the study show that: (1) The low motivation of children to go to school is a factor that causes children to drop out of school in Braja Luhur Village in 2021. This can be seen from the percentage of children's low motivation of 60%. (2) The low interest of children to go to school is a factor causing children to drop out of school in Braja Luhur Village in 2021. This can be seen from the low percentage of children's interest at 54%. (3) The low income of parents of children dropping out of school is a factor causing children to drop out of school in Braja Luhur Village in 2021. This can be seen from the low percentage of income of 72%. (4) The lack of parental attention is a factor that causes children to drop out of school in Braja Luhur Village in 2021. This can be seen from the low percentage of parental attention of 54%.